Why and where?-Delay in Tuberculosis care cascade: A cross-sectional assessment in two Indian states, Jharkhand, Gujarat - Sandul Yasobant; Sandul Yasobant; Harsh Shah; Priya Bhavsar; Jay Patel; Somen Saha; Anish Sinha; Tapasvi Puwar; Yogesh Patel; Deepak Saxena; Deepak Saxena (Frontiers Media S.A., 2023)
Tuberculosis (TB) is the second leading cause of death due to infectious diseases globally, and delay in the TB care cascade is reported as one of the major challenges in achieving the goals of the TB control programs. The main aim of this study was to investigate the delay and responsible factors for the delay in the various phases of care cascade among TB patients in two Indian states, Jharkhand and Gujarat. This cross-sectional study was conducted among 990 TB patients from the selected tuberculosis units (TUs) of two states. This study adopted a mixed-method approach for the data collection. The study targeted a diverse profile of TB patients, such as drug-sensitive TB (DSTB), drug resistance TB (DRTB), pediatric TB, and extra-pulmonary TB. It included both public and private sector patients. The study findings suggested that about 41% of pulmonary and 51% of extra-pulmonary patients reported total delay. Delay in initial formal consultation is most common, followed by a delay in diagnosis and treatment initiation in pulmonary patients. While in extra-pulmonary patients, delay in treatment initiation is most common, followed by the diagnosis and first formal consultation. DR-TB patients are more prone to total delay and delay in the treatment initiation among pulmonary patients. Addiction, co-morbidity and awareness regarding monetary benefits available for TB patients contribute significantly to the total delay among pulmonary TB patients. There were system-side factors like inadequacy in active case findings, poor infrastructure, improper adverse drug reaction management and follow-up, resulting in delays in the TB care cascade in different phases. Thus, the multi-disciplinary strategies covering the gambit of both system and demand side attributes are recommended to minimize the delays in the TB care cascade.